COMMUNICATION EFFECTIVENESS AND SERVICE QUALITY ON PATIENT SATISFACTION AND ITS IMPLICATIONS ON PATIENT SATISFACTION - Sri Rochani Mulyani; rulia; vip paramarta; Endang Maryam Zamilah El Hakim (Universitas Majalengka, 2025)
Based on preliminary studies, 8% of respondents stated that communication was poor, 18% stated that service quality was poor, 28% were dissatisfied, and 8% stated that they would’t visit again. The type of research was quantitative research with a descriptive-verificative approach using path analysis. Based on the questionnaire results, communication and service quality were rated as very good, patient satisfaction was rated as very satisfied, and patients stated they would visit the health center again. There was a significant influence between communication and patient satisfaction (p-value 0.006), service quality and patient satisfaction (p-value 0.001), communication and service quality simultaneously on patient satisfaction (p-value 0.001), patient satisfaction on patient visits (p-value 0.001), direct communication on patient visits (p-value 0.042), direct service quality on patient visits (p-value 0.001), indirect communication on patient visits through patient satisfaction (p-value 0.031), and indirect service quality on patient visits through patient satisfaction (p-value 0.005).